2019
DOI: 10.3390/molecules24122250
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction of Biomass and Upgrading of Bio-Oil: A Review

Abstract: The liquefaction of biomass is an important technology to converse the biomass into valuable biofuel. The common technologies for liquefaction of biomass are indirect liquefaction and direct liquefaction. The indirect liquefaction refers to the Fischer–Tropsch (F–T) process using the syngas of biomass as the raw material to produce the liquid fuel, including methyl alcohol, ethyl alcohol, and dimethyl ether. The direct liquefaction of biomass refers to the conversion biomass into bio-oil, and the main technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(47 citation statements)
references
References 220 publications
(249 reference statements)
0
41
0
Order By: Relevance
“…The calculating kinetic parameters of ketonization reaction of CD 3 COOH, CH 3 COOH and CH 3 13 COOH on the hCeSi surface showed that the pre-exponential factors have close values within the limits of the same order~10 9 as in the cause of reaction series of carboxylic acids on the lCeSi surface (Table 4). This result allows using Equation 5for calculation of DKIE of formation of acetone isotopomers from deuterated acetic acid in comparison with formation acetone from nonlabeled acetic acid.…”
Section: Study Of the Magnitude And The Origin Of Dkiementioning
confidence: 94%
See 2 more Smart Citations
“…The calculating kinetic parameters of ketonization reaction of CD 3 COOH, CH 3 COOH and CH 3 13 COOH on the hCeSi surface showed that the pre-exponential factors have close values within the limits of the same order~10 9 as in the cause of reaction series of carboxylic acids on the lCeSi surface (Table 4). This result allows using Equation 5for calculation of DKIE of formation of acetone isotopomers from deuterated acetic acid in comparison with formation acetone from nonlabeled acetic acid.…”
Section: Study Of the Magnitude And The Origin Of Dkiementioning
confidence: 94%
“…Catalytic pyrolysis can effectively convert second-generation feedstocks (lignocellulose, waste oils, fats, algae, agricultural and forest residues, etc.) into bio-oil or pyrolysis oil [1][2][3][4][5][6][7]. The potential for the use of biomass resources of second-generation feedstocks in Europe is very high [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global consumption of transportation fuels, lubricants, and chemicals amid the depletion of petroleum reserves is leading to a growing demand for alternative hydrocarbon sources. These non-petroleum feedstocks include natural gas and coal, as well as renewable biomass and urban wastes [1]. All of them can be converted into clean hydrocarbons via syngas production followed by Fischer-Tropsch synthesis (FTS).…”
Section: Introductionmentioning
confidence: 99%
“…It is a dark brown and viscous liquid, mainly composed of acids, alcohols, aldehydes, esters, ketones, phenols, and guaiacol. Zhang et al (2019) summarized bio-oil main characteristics in a table, comparing it to heavy petroleum fuel oil.…”
Section: Introductionmentioning
confidence: 99%